2021
DOI: 10.3390/molecules26164878
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Method for the Biomonitoring of Mercury in Bees and Beehive Products by Cold Vapor Atomic Fluorescence Spectrometry

Abstract: Bees and their products are useful bioindicators of anthropogenic activities and could overcome the deficiencies of air quality networks. Among the environmental contaminants, mercury (Hg) is a toxic metal that can accumulate in living organisms. The first aim of this study was to develop a simple analytical method to determine Hg in small mass samples of bees and beehive products by cold vapor atomic fluorescence spectrometry. The proposed method was optimized for about 0.02 g bee, pollen, propolis, and royal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 52 publications
(143 reference statements)
0
9
0
Order By: Relevance
“…Although studies have already been carried out on the chemical characterization and accumulation of toxic substances in honey [ [24] , [25] , [26] , [27] , [28] ], few studies have been conducted on mercury content in Italian honey, which is the only country in the world that produces more than 30 varieties of honey [ 10 ], besides all of high physicochemical quality [ 26 , [29] , [30] , [31] ]. To the best of our knowledge, only three studies were carried out in Italy on Hg content in honey [ [32] , [33] , [34] ].…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have already been carried out on the chemical characterization and accumulation of toxic substances in honey [ [24] , [25] , [26] , [27] , [28] ], few studies have been conducted on mercury content in Italian honey, which is the only country in the world that produces more than 30 varieties of honey [ 10 ], besides all of high physicochemical quality [ 26 , [29] , [30] , [31] ]. To the best of our knowledge, only three studies were carried out in Italy on Hg content in honey [ [32] , [33] , [34] ].…”
Section: Introductionmentioning
confidence: 99%
“…THg concentrations in our samples are all below WHO standards (Joint FAO/WHO Expert Committee, 2011). Compared with previous THg concentrations in bees and bee products, it is unlikely that beekeeping products from North American honey bees pose a risk of Hg to human health (Astolfi et al., 2021; Fischer et al., 2021).…”
Section: Resultsmentioning
confidence: 86%
“…(Zaric et al., 2018), which is comparable to temperate forest invertebrates at relatively low trophic levels in North America (Tsui et al., 2019). However, no study has reported MeHg in honey bees so far (Astolfi et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that bees and their products could be useful bioindicators of anthropogenic activities and could overcome some of the deficiencies of air quality networks. To this end, researchers 129 have developed a suitable sample preparation method for the determination of Hg in bees and beehive products (pollen, propolis, royal jelly, beeswax, honey, honeydew) by CV-AFS. Results were obtained from small sample masses (20–100 mg) heated with a mixture of 0.5 mL HCl, 0.2 mL HNO 3 , and 0.1 mL H 2 O 2 in a water bath at 95 °C, which was made up to a final volume of 5.0 mL.…”
Section: Progress With Analytical Techniquesmentioning
confidence: 99%